Faktor-Faktor Penentu Kebijakan Hutang: Studi pada Perusahaan Barang Konsumsi di Indonesia - Delicia Zora Damara, Nurainun Bangun (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to examined the effect of asset stucture, liquidity and non-debt tax shields to debt policy on consumer goods companies listed on Indonesia stock exchange since 2018-2020. This study method used was descriptive quantitative and 49 selected companies observated by using the purposive sampling method. Data processing in this study was carried out using the eviews 12 application. The results of this study showed that all independent variables asset stucture, liquidity and non-debt tax shields have a significant affect on debt policy.